Using Cooperative Learning to Teach the Sustainable Development Goals - Jacobs, George M; Zhu, Chenghao; Chau, Meng Huat; Guo, Qingli; Roe, Jasper (Autonomy and Responsibility Journal of Educational Sciences, 2023)
This article advocates for the use of cooperative learning by students and others toward the achievement of the United Nations’ Sustainable Development Goals (SDGs). First, the Goals are explained. Second, background is provided on cooperative learning, including explanation of eight cooperative learning principles and exemplification of how one cooperative learning technique might mobilize the eight principles. Third, how cooperative learning fits with student centered learning is explored. Fourth, two cooperative learning techniques are explained for their particular relevance to efforts to achieve the SDGs. These techniques are Group Investigation and Cooperative Debate. Fifth, two cooperative learning principles, positive interdependence and cooperation as a value, and their links to SDGs receive further exploration. Finally, we consider cooperative learning as a Swiss Army Knife and discuss its versatility with SDG examples.